The usefulness of total body protein mass models for adolescent athletes - Silva, Analiza M.; Campa, Francesco; Sardinha, Luís B. (Frontiers in Nutrition, 2024)
The present study aimed to assess the utility of a less laborious technique in the estimation of total body protein (TBPro) in young athletes, using a multi-compartment model as the criterion method. A total of 88 (49 boys and 39 girls) adolescent athletes (age: 15.2 ± 1.5 yrs; body mass index: 21.2 ± 2.7 kg/m 2 ) participated. A 6-compartment model was used as the reference method (TBProReference) involving air displacement plethysmography for body volume, dual energy X-ray absorptiometry (DXA) for bone mineral content, and deuterium dilution for total body water (TBW). Alternatively, DXA TBPro models were used as TBPro = Lean-Soft mass (LSM) -HFFFM x Fat-Free Mass (FFM) -Ms -G, where LSM and FFM were assessed by DXA, HFFFM is the hydration fraction of the FFM using measured TBW or assumed TBW (adult fraction of 0.732; Lohman's constants or mean observed HFFFM), Ms is soft-tissue minerals (Ms = 0.0129 x HFFFM x FFM), and G is glycogen calculated as 0.044 x (LSM -HFFFM x FFM -Ms)]. Maturation level was determined by self-assessment. TBPro obtained from DXA using the assumed HFFFM explained 73% to 77% of the variance compared to TBProReference while using the mean values of measured HFFFM DXA model explained 53 and 36%, respectively for boys and girls. Larger bias 8.6% (boys) and 25.8% (girls) and limits of agreement were found for DXA model using measured HFFFM (boys, 66.9 and girls, 70%) compared to an assumed HFFFM (bias ranged from 1.5% to 22.5% and limits of agreement ranged from 31.3 to 35.3%). Less complex and demanding total body protein DXA models with the assumed HFFFM are valid alternatives for assessing this relevant FFM component in groups of adolescent athletes but are less accurate for individual results. Though future studies should be conducted to test the usefulness of these models in longitudinal and experimental designs, their potential to provide an estimation of protein mass after exercise and diet interventions in young athletes is anticipated.